Brincar de colorir e desenhar: procedimento de ensino para criança com TEA - Albuquerque, Isis de (Universidade Federal de São Carlos, 2020)
Children diagnosed with autism spectrum disorder (ASD) may present difficulties in playing behavior, requiring intervention and teaching procedures aimed at learning this behavior. Having regard to the importance of colouring and drawing for academic skills, this study has drawn up and implemented a teaching programme, which took into account the sensory and behavioural aspects necessary for teaching colouring and drawing, aiming to make the behavior of coloring and drawing naturally reinforcing for children with ASD. The study included three children diagnosed with ASD, two boys and a girl, who had an aversion to the use of graphic material. The results present the teaching programs developed by playing with coloring and drawing and indicate that the application of these programs favored the spontaneous choice of graphic material to color and draw in the three participants and increase the time of functional use of this material. It was also observed a reduction in fugue and avoidance behaviors in relation to graphic material and a reduction in the use of prompts during teaching sessions. The coloring and drawing became part of the repertoire of games of the participants, who spontaneously chose the graphic material for functional use, verbalizing phrases that indicated satisfaction with the play, expressing smiles and maintaining a relaxed posture while coloring and drawing
Play coloring and drawing: teaching procedure for child with ASD
Keywords: Programa de ensino; Transtorno do Espectro Autista; Análise do comportamento; Integração sensorial; Brincar; Colorir e desenhar; Teaching program; Autism Spectrum Disorder; Behavior analysis; Sensory integration; Play; Coloring and drawing; CIENCIAS HUMANAS::PSICOLOGIA